Pengaruh Pengungkapan Tanggung Jawab Sosial Perusahaan Terhadap Tingkat Pengembalian Saham - Atiqah Atiqah (Akuntabilitas, 2016)
The purpose of this research is to examine the effect Of Corporate Social Responsibility Disclosure Through Risk To Stock Return. In this study, using the GRI standard as a way to measure a company's corporate social responsibility. Samples company is an enterprise consumer goods are listed on the Stock Exchange in the period from 2010 to 2014 so that the total sample at the 5-year period is 60 samples. The research method uses multiple linear regression analysis to determine the relationship of more than one independent variable on the dependent variable. Based on the results of statistical performed by t-tests and F test, shows that CSR and risk have effect to return with significance alpha 1%. Corporate Social Responsibility Disclosure have effect Through Risk To Stock Return. ROA as a control variable doesn’t have effect to stock return.